Evaluation of AgriMune Liquid on Growth Performance of Commercial Nursery Pigs - Andres F. Tolosa; Joel M DeRouchey; Jason C. Woodworth; Mike D. Tokach; Robert D. Goodband; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2021)
A total of 1,188 pigs (L337 × 1050; PIC; initial BW of 11.1 lb) were used in a 40-d trial to determine the effect of a combination of mannan oligosaccharides, yeast culture, and beta-glucans (AgriMune Liquid; AFI-Agri Feed International, L.L.C., Rockwell, IA) on growth performance, morbidity, and mortality of pigs during the nursery period. Pigs were weaned at approximately 21 d of age and placed in pens (27 pigs per pen) based on initial BW. Pens were randomly assigned to 1 of 2 treatments in a randomized complete block design with 22 pens (replications) per treatment. Treatments consisted of the control in which pigs only received water through the water line, or pigs were provided the combination of mannan oligosaccharides, yeast culture, and beta-glucans in the water at a rate of 4 mL per head per day (mL/hd/d) from day 1 to 4 and then 2 mL/ hd/d from d 5 until the end of the experiment. All pigs were fed the same commercial diets in three phases for the duration of the trial. Overall, from d 0 to 40, pigs on the control treatment tended (P= 0.095) to have increased ADFI compared with pigs provided mannan oligosaccharides, yeast culture, and beta-glucans through the water, with no evidence of difference (P>0.10) on ADG, F/G, or BW. For mortality and morbidity, there was no evidence of difference (P>0.05) observed. In summary, there was no effect on overall nursery performance when a combination of mannan oligosaccharides, yeast culture, and beta-glucans was provided in the water.
Keywords: beta-glucans; mannan oligosaccharides; nursery pigs; yeast